Evaluation of optimal parameters on laser drilling of synthesized titanium composite. (2022) - Kannan, R.; Sathish, S.; Kumar, A.Sathish; Girisha, L.; Krishnamoorthy, S.; Alex, S.Rahul; Subbiah, R.
Highlights: Laser drilling is the efficient process and recent technology which is used in manufacturing industries. The dimensional accuracy and finish is attained from laser drilling process. In this paper, optimization and laser drilling is conducted on synthesized titanium composite. It has consisted of different alloying elements such as titanium, silicon, vanadium. Three alloying elements are reinforced with 1.5 wt% of boron carbide. The substance properties are evaluated with suitable arrangements. Laser power, cutting speed and pulse frequency was used to evaluate the rate of metal removal (RMR) during drilling process. Taguchi method and variance analysis was used to optimize the laser drilling factors and effect of process factors. Abstract: Laser drilling is the efficient process and recent technology which is used in manufacturing industries. The dimensional accuracy and finish is attained from laser drilling process. In this paper, optimization and laser drilling is conducted on synthesized titanium composite. It has consisted of different alloying elements such as titanium, silicon, vanadium. Three alloying elements are reinforced with 1.5 wt% of boron carbide. The substance properties are evaluated with suitable arrangements. Laser power, cutting speed and pulse frequency was used to evaluate the rate of metal removal (RMR) during drilling process. Taguchi method and variance analysis was used to optimize the laser drilling factors and effect of process factors. The optimal rate of metal removal was attained at 2200 W of laser power, 6000 Hz of frequency and 4000 mm/min of cutting speed. Laser power was produced largest effect on rate of material removal (86.95 %).